Neuropsychological and Educational Profile of Children with Dyscalculia and Dyslexia: A Comparative Study - Pestun,Magda Solange Vanzo (2019)
Abstract This paper aims to compare the neuropsychological and educational profiles of Brazilian children with dyscalculia (n = 8), dyslexia (n = 13) and without learning disabilities (n = 12). The neuropsychological profile was composed of: (a) intelligence - assessed by the Wechsler Intelligence Scale for Children (WISC-III); (b) attention - WISC-III Coding and Symbol Search subtests; (c) executive functions - Digit Span (backward order) and WISC-III Arithmetic subtests, Pseudoword Repetition Test for Brazilian Children, Stroop Test and Wisconsin Card Sorting Test; (d) memory - WISC-III Digit Span subtest (forward order) and Rey Complex Figures. The educational profile was composed of reading, writing and mathematics, assessed by the Academic Performance Test and the Arithmetic Test. It was found that the groups with dyscalculia and dyslexia did not differentiate in any of the neuropsychological abilities, only in the reading and writing abilities. Neuropsychological variables that could explain these results were discussed.